Strategi Guru Akidah Dan Akhlak Dalam Meningkatkan Kedisiplinan Belajar Siswa di MTS Nurul Iman Padang Reba - Fadillah, M. Ihsan; Hasbi, Syaukhani (Jurnal Manajemen Akuntansi (JUMSI), 2024)
This thesis discusses about Teachers' Strategy of Akhlak In Improving Student Discipline In Madrasah Tsanawiyah Nurul Iman Padang Reba Regency, this research is a qualitative research by using primary and secondary data source. To obtain the data the researcher use Obsevation, Documentation, and interview method. The purpose of this study is to find out how the state of student learning discipline, constraints of moral teachers, and how the strategy of moral aqid in improving student learning discipline The result of the research shows that the condition of student learning discipline in Madrasah Tsanawiyah Nurul Iman Padang RebaÂ  is still weak student intereststudents lack self introspection, and still weak student punishment. Constraints of teachers ie students like to make noise in the classroom, there are students who smoke and bring mobile phones and ditching into the classroom. The teacher'sstrategy is to provide guidance, the teacher gives advice, and the teacher sanction the students who violate the discipline.